DEVELOPMENT OF THE MANDANGIN ISLAND VILLAGE WEBSITE AS A MEANS OF INFORMATION AND A MEANS OF RECEIVING RESIDENTS' COMPLAINTS - Sofiyulloh; Syahroni, Abd Wahab; Rachmatullah, Sholeh; Rachman, Anang Faktchur; Ramadhani, Nilam; Zumam, Wildona (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to develop a web-based village information system for Pulau Mandangin to improve the dissemination of information and facilitate residents in submitting complaints online, addressing the long-standing challenge of ineffective communication between villagers and local authorities. Method: The system was designed using the CodeIgniter 4 framework due to its lightweight structure and efficiency in web application development. Key features include village profile information, historical background, vision and mission, news updates, official announcements, organizational structure, and an integrated online complaints submission module. System performance was evaluated using black box testing, and user satisfaction was assessed through a Likert-scale survey. Results: Black box testing confirmed that all system functionalities operated correctly and as intended. The user satisfaction survey produced a score of 77.5%, categorized as “agree,” indicating a high level of acceptance and perceived usefulness among residents. Novelty: This research provides a practical digital solution for remote island communities with limited IT adoption, presenting an accessible and community-oriented platform that enhances transparency, communication efficiency, and public service delivery at the village level.